Telaah Literatur Akad Salam pada Sistem Pemesanan Barang di Shopee - Indah Aminah Putri; Lilia Afriani; Taufik Kurahman; Rosnani Siregar (Multiverse: Open Multidisciplinary Journal, 2025)
Prior to the emergence of digital technology and online marketplaces, commercial transactions had already existed, albeit through different mechanisms and modes of exchange. In the contemporary digital economy, electronic commerce platforms have transformed traditional trading practices, raising questions regarding their compatibility with Islamic commercial contracts. This study aims to examine the implementation of the Salam contract in the goods ordering system on Shopee. Employing a qualitative research design based on a systematic literature review, data were collected from relevant academic journals, books, and scholarly sources discussing Salam contracts and e-commerce transactions. The findings indicate that Shopee’s transaction mechanism reflects the essential characteristics of a Salam contract, particularly the requirement of full advance payment prior to the delivery of goods at a mutually agreed time. Buyers complete the payment in advance through various payment channels, after which the goods are delivered to the buyer, and funds are released to the seller upon confirmation of product conformity. The study argues that Shopee’s transaction system demonstrates functional alignment with the principles of the Salam contract, although continuous evaluation is necessary to ensure full compliance with Islamic commercial jurisprudence in digital marketplaces.